2016
DOI: 10.1159/000441953
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Topical, Systemic and Combined Application of Antioxidants on the Barrier Properties of the Human Skin

Abstract: Background: The formation of free radicals in human skin by solar ultraviolet radiation is considered to be the main reason for extrinsic skin aging. The antioxidants in human tissue represent an efficient protection system against the destructive action of these reactive free radicals. In this study, the parameters of the skin, epidermal thickness, stratum corneum moisture, elasticity and wrinkle volume, were determined before and after the treatment with antioxidant- or placebo-containing tablets and creams.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 36 publications
0
22
0
Order By: Relevance
“…The modulation of serum lipid profiles by almond supplementation has been studied in detail. Conversely, their effects on the skin's lipid barrier function are under studied, although alteration of the skin barrier can improve several skin features including wrinkles (Lademann et al, 2016;Yoon et al, 2016). The sebaceous glands, housed within the dermis, are in close contact to systemic blood circulation.…”
Section: Introductionmentioning
confidence: 99%
“…The modulation of serum lipid profiles by almond supplementation has been studied in detail. Conversely, their effects on the skin's lipid barrier function are under studied, although alteration of the skin barrier can improve several skin features including wrinkles (Lademann et al, 2016;Yoon et al, 2016). The sebaceous glands, housed within the dermis, are in close contact to systemic blood circulation.…”
Section: Introductionmentioning
confidence: 99%
“…In support of this notion, the recent report by Lademann et al, in 2016, showed that antioxidants positively influenced the barrier function of human skin [87]. For example, antioxidants significantly increased epidermal thickness, elasticity, and stratum corneum moisture content [87].…”
Section: Equol Is Delivered Into Human Skin Via a Unique "Reservoir" mentioning
confidence: 92%
“…Undoubtedly, equol may enhance the skin's barrier function and cellular integrity via its topical application and sustained delivery mechanism [12,82]. In support of this notion, the recent report by Lademann et al, in 2016, showed that antioxidants positively influenced the barrier function of human skin [87]. For example, antioxidants significantly increased epidermal thickness, elasticity, and stratum corneum moisture content [87].…”
Section: Equol Is Delivered Into Human Skin Via a Unique "Reservoir" mentioning
confidence: 98%
“…Measurements by this device were conducted on an area with a diameter of 50 mm by the miniaturized sensor that was placed in between the textile and the skin upon occlusion measuring the temperature and relative humidity at intervals of 20 seconds in 20 subjects. For comparison, the temperature and hydration were also measured before and after the 60 minute textile application using established measurement devices, such as an infrared thermometer (Raytek ® , Fluke Process Instruments GmbH, Berlin, Germany), for the assessment of the temperature and a Corneometer CM 825 (Courage ‐ Khazaka Electronic, Cologne, Germany), for the assessment of the skin hydration . These measurements were performed on the palm, which is characterized by a high sweat gland density.…”
Section: Methodsmentioning
confidence: 99%
“…For comparison, the temperature and hydration were also measured before and after the 60 minute textile application using established measurement devices, such as an infrared thermometer (Raytek ® , Fluke Process Instruments GmbH, Berlin, Germany), for the assessment of the temperature and a Corneometer CM 825 (Courage -Khazaka Electronic, Cologne, Germany), for the assessment of the skin hydration. 34 These measurements were performed on the palm, which is characterized by a high sweat gland density.…”
Section: Transepidermal Water Loss (Tewl)mentioning
confidence: 99%